PRIMARY TEACHERS’ AND STUDENTS’ PERCEPTION ON THE USE OF ICT-BASED INTERACTIVE GAME IN ENGLISH LANGUAGE TEACHING - Asnadi, I.W.S.W.; Ratminingsih, N.M.; Myartawan, I.P.N.W. (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2018)
This study aimed at investigating (1) the teachers’ perception on the use of ICT-based Interactive Game in teaching English, and (2) the perception of the sixth graders on the use of ICT-based Interactive Game toward their learning motivation and English achievement. Methodically, this study was quantitative research in which survey was employed. In order to collect the data, different questionnaires were administered primarily as the instrument both for teachers and students. The samples of this study were 6 English teachers and 152 students of the sixth grade in 6 primary schools in Sukasada District, Buleleng Regency. Prior to data analysis, the results of this study were computed by finding out the percentage of each item and its average in order to withdraw the conclusion descriptively. The results were (1) there was a positive perception of the teachers with regard to the use of ICT-based Interactive Game in teaching English to the sixth grade of primary schools in the cluster IV and V in Sukasada District and (2) there was positive perception of the students on the use of ICT-based Interactive Game toward their learning motivation and English achievement.